Risk Management in Client Acceptance Decisions - Johnstone, Karla M.; Bedard, Jean C. (The Accounting Review, 2003)
This paper examines whether risk-management strategies (specifically, the use of specialist personnel and higher billing rates) moderate the effect of risk on client acceptance decisions, thereby assisting auditors in bringing prospective client relationships to acceptable risk/return levels. We propose a conceptual model of the client acceptance decision process, and use archival data on one firm's actual client acceptance decisions to test the model. Our results demonstrate the selective use of risk-management strategies in the client acceptance decision, based on the nature of the risks present for each particular client. Specifically, plans to charge a higher billing rate are associated with a reduction in the negative relationship between client acceptance likelihood and both going-concern risk and public trading status, and plans to assign specialist personnel are associated with a reduction in the negative relationship between client acceptance likelihood and both fraud risk and error risk. Therefore, we provide evidence that while risky clients are less likely to be accepted overall, the application of particular risk-management strategies to particular risks increases the likelihood of accepting such clients.